2012
DOI: 10.1097/ico.0b013e31821ea667
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, Objective, Multimodal Tear Dynamics Evaluation of 5 Over-the-Counter Tear Drops in a Randomized Controlled Trial

Abstract: Noninvasive multimodal imaging has the potential to evaluate tear dynamics and the efficacy of artificial tears objectively. Certain artificial tear components and the temporary increase in tear volume after instillation of artificial tears may contribute to transient reduction of visual quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
3
21
1
2
Order By: Relevance
“…In patients with dry eye, tear meniscus measurements obtained after the instillation of CMC took longer to return to the baseline levels compared with those in normal subjects. 27 Moreover, Yuan et al 32 reported that patients with aqueous tear-deficient dry eye had decreased tear meniscus dynamics during normal and delayed blinking. The effects of instillation of ophthalmic solutions would be different between patients with and without dry eye because of differences in the baseline levels, tear clearance rate, and blinking.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with dry eye, tear meniscus measurements obtained after the instillation of CMC took longer to return to the baseline levels compared with those in normal subjects. 27 Moreover, Yuan et al 32 reported that patients with aqueous tear-deficient dry eye had decreased tear meniscus dynamics during normal and delayed blinking. The effects of instillation of ophthalmic solutions would be different between patients with and without dry eye because of differences in the baseline levels, tear clearance rate, and blinking.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Ridder et al 26 investigated both the short-term effect and long-term daily use of artificial tears for up to 2 weeks and reported that the long-term effect resulted in less of a short-term effect in patients with dry eye. However, the therapeutic effect of eye drops specifically prescribed for dry eye on the optical quality has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…We previously investigated the short‐term effects of five different over‐the‐counter tear drops on optical quality and found that the effect varies depending on the composition of artificial tears and the severity of dry eye (Tung et al. ). Differences in dry eye diagnostic criteria and methodology among studies may have also contributed to the difference including the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Tung et al. () reported that instillation of a certain type of artificial tear (polyethylene glycol drops) worsened visual quality along with an increase in tear meniscus dimensions in patients with aqueous‐deficient dry eye. According to previous animal studies, diquafosol increases the tear meniscus dimension 15 min after instillation in normal cats (Murakami et al.…”
Section: Discussionmentioning
confidence: 99%